Non-observance of cooperative principles in SpongeBob SquarePants’ episode “Home Sweet Pineapple” - Destra Wibowo Kusumo (UPT P2M Politeknik Negeri Malang, 2016)
This article attempts to seek out the non-observance of cooperative principles in animated series SpongeBob SquarePants episode ‘Home Sweet Pineapple’. The objects of the study is the spoken utterances by all the characters. The study applied linguistic and descriptive qualitative design as proposed by Sudaryanto (1993), Moleong (2004), Dorney (2007), and Lodico (2010). Note-taking technique is used in the data collection process. In the data analysis, the researcher employed the notion of non-observance of cooperative principles as proposed by Grice (1975), Thomas (1995), Cruse (2000), Grundy (2000), and Cutting (2002). The study results in three findings. Firstly, there are three kinds of non-observances of all four maxims: infringement, flout, and violation of four maxims. Next, Squidward tends to violate the maxims, whereas SpongeBob and Patrick tends to flout the maxims. Finally, the nonobservance of the cooperative principles are successful in creating the humorous effect to the viewers.